Phytochemicals and Effect of Blanching Time on Oxalate and Phytate Content in Leaves of Some Non-conventional Vegetables in Gombi Local Government Area, Adamawa State, Nigeria - A. H. Boda; B. F. Dowell; D. W. Malgwi; W. Emmanuel (Journal of Applied Sciences and Environmental Management)
The objective of this paper was to evaluate the phytochemicals and effect of blanching time on oxalate and phytate content in leaves of some non-conventional vegetables in Gombi Local Government Area, Adamawa State, Nigeria using appropriate standard methods. Data obtained reveals the presence of flavonoids, phenols, steroids and alkaloids in the vegetables. Saponins were found in bitter leaf, kenaf leaf and roselle leaf but absent in moringa and cassia tora leaf. The highest amount of oxalate was present in roselle leaves (17.10±2.30 mg/100 g), followed by moringa leaves (12.30±1.30 mg/100 g), and spinach (10.00±0.85 mg/100 g) of the unblanched samples. The greatest decrease in oxalate concentrations was observed in vegetable samples that were blanched for six minutes. As the blanching time increased, the phytate contents of the vegetables under study decreased. High levels of phytate were detected in unblanched samples of spinach (22.20±1.10 mg/100 g), kenaf leaves (22.00±1.10 mg/100 g), and roselle leaves (22.00±1.80 mg/100 g). In terms of phytate and oxalate content, the concentrations in the examined veggies were found to be within the allowable limit of 25 mg/100 g. All six vegetable samples had flavonoids, phenols, steroids, and alkaloids, according to the phytochemical screening. The hazards of exposure to oxalate and phytate contents can be decreased by changing dietary practices, and the blanching duration of vegetables that are frequently consumed should be continuously monitored for oxalate and phytate content.